Apolipoprotein E Genetic Variation and Its Association With Cognitive Function in Rural-Dwelling Older South Africans - Soo, Cassandra C.; Farrell, Meagan T.; Tollman, Stephen; Berkman, Lisa; Nebel, Almut; Ramsay, Michèle (Frontiers in Genetics, 2021)
Apolipoprotein E (APOE) 𝜀4 allele carrier status is well-known for its association with an increased likelihood of developing Alzheimer’s disease, but its independent role in cognitive function is unclear. APOE genetic variation is understudied in African populations, hence this cross-sectional study in a rural South African community, examined allele and genotype frequencies, and their associations with cognitive function. Cognitive function was assessed using two different screening methods to produce a total cognition score, and four domain-specific cognition scores for verbal episodic memory, executive function, language, and visuospatial ability. Cognitive phenotype and APOE genotype data were used to determine whether APOE variation was significantly associated with cognitive function in this population. Observed allele frequencies for 1776 participants from the HAALSI study (age 40-80 years (mean=56.19); 58.2% female) were 58.1% (𝜀3), 25.4% (𝜀4) and 16.5% (𝜀2). Allele distributions were similar to the African super population, but different from all non-African super populations from the 1000 Genomes Project. The 𝜀3 homozygous genotype was most common (34.9%) and used as the base genotype for comparison in regression models. Four models were tested for each of the five cognitive phenotypes to explore association of APOE variation with cognitive function. In the first model assessing association with all genotypes for all individuals, marginally significant associations were observed for 𝜀2 homozygotes where executive function scored higher by ~0.5 standard deviations (p=0.037, SE=0.23), and for 𝜀3/𝜀4 where visuospatial ability lower (p=0.046, SE=0.14). These did not survive correction for multiple testing. Regional African population differences are observed at the APOE locus. Marginally significant associations between APOE genotype, and executive function and visuospatial ability indicate the need for larger studies to better examine these associations in African populations. Furthermore, longitudinal data could shed light on APOE genetic association with rate of change, or decline, in cognitive function.